Comparing the effects of traditional resistance training and functional training on the bio-motor capacities of female elite taekwondo athletes - Leila Khazaei; Abdolhossein Parnow; Sadegh Amani-shalamzari (BMC, 2023)
Abstract Background The capabilities of the biomotors are essential to the success of the taekwondo athlete. This study aimed to compare eight weeks of functional training and traditional resistance on the bio-motor capacities of elite female taekwondo athletes. Methodology Seventeen elite taekwondo athletes (mean age = 21.7 years, mean height = 167.2 cm and mean weight = 60.8 kg) volunteered to participate in the study. They were randomly divided into two groups: functional training (FT) and traditional resistance training (TRT). Participants trained for 8 weeks, 3 sessions per week, for 75-90 min. Aerobic power, anaerobic power, speed, reaction time, agility, muscle power, dynamic balance, flexibility, upper and lower body muscle strength, core and upper body muscle endurance, and blood lactate level were measured before and after training programs. Results Non-significant differences were observed in all indicators between the FT and TRT groups (P > 0.05). Both groups showed significant improvement in time-related outcomes except for fatigue and flexibility (P > 0.05). There was significant progress in both groups in aerobic power, muscle power, speed, agility, reaction time, lower body strength, upper body strength, dynamic balance of the right leg, and dynamic balance of the left leg indices from pre to post-tests. The FT group displayed significant improvement in peak power (P = 0.006) and mean power (P = 0.015) from pre- to post-test. Conclusion Both interventions improved most biomotor abilities in elite female taekwondo athletes. It should be noted that since muscle power is vital for taekwondo, therefore, it is recommended to include FT in the taekwondo workout program.